Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) terhadap Kombinasi Pupuk NPK dengan Pupuk Organik Cair Limbah Ikan Nila - Fikriansyah, Rezan; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
1This research aims to determine the best combination of NPK fertilizer with tilapia waste liquid organic fertilizer to the growth of oil palm seeds. This research was conducted at UPT. Experimental Garden, Agriculture Faculty, University of Riau, Pekanbaru. The research was conducted from May to September 2019. This research was conducted using a completely randomized design (CRD) with 7 treatments and 3 replications. The treatments used were NPK fertilizer 2.50 g per plant (control), NPK fertilizer 1.25 g per plant + LOF tilapia waste 25%, NPK fertilizer 1.25 g per plant + LOF tilapia waste 50%, NPK fertilizer 1.25 g per plant + LOF tilapia waste 75%, NPK fertilizer 2.50 g per plant + LOF tilapia waste 25%, NPK fertilizer 2.50 g per plant + LOF tilapia waste 50% and NPK fertilizer 2.50 g per plant + LOF tilapia waste 75%. Parameters observed were seedling height, number of seed leaves, seed bulb diameter, seedling leaf area, seedling root volume, seedling root shoot ratio and seed dry weight. The data obtained were analyzed using analysis of variance and continued with the Duncan's New Multiple Range Test(DNMRT) at the 5% level. The results showed that the combination of NPK fertilizer treatment with tilapia waste LOF affected the parameters of seed height, number of leaves, bulb diameter, leaf area, root volume, root shoot ratio and seed dry weight. The combination of NPK fertilizer 1.25 g per plant + LOF tilapia waste 25% is the best treatment to increase the growth of oil palm seedlings. Keywords: Oil palmseeds, NPK fertilizer, tilapia waste liquid organic fertilizer